The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1097/00005053-199601000-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Dependent Personality and Interpersonal Problems

Abstract: At the core of the dependent personality disorder lies an excessive reliance on other people for support, direction, and nurturance. However, because of their interpersonal style, many patients high in dependency have difficulties establishing and maintaining close interpersonal relationships. The present study examined interpersonal problems related to the dependent personality disorder. The relationships between dependency and interpersonal problems were examined in 43 adult psychiatric inpatients and 66 non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 57 publications
4
45
0
1
Order By: Relevance
“…It is comprised of three underlying dimensions: emotional reliance on others, lack of social self-confidence, and assertion of autonomy. More recently, research has shown that degrees of interpersonal dependency tend to covary with emotional distress (Nietzel & Harris, 1990;Santor & Patterson, 2004) and like with other distressed emotional states, it may be possible that loneliness aggravates maladaptive social functioning in individuals exhibiting excessive dependency on others (Overholser, 1996). Individuals with dependent personalities may be at risk for other psychological disorders (Bornstein & Greenberg, 1991;Nietzel & Harris, 1990;Skodol, Gallagher, & Oldham, 1996;Vaillant, 1980).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is comprised of three underlying dimensions: emotional reliance on others, lack of social self-confidence, and assertion of autonomy. More recently, research has shown that degrees of interpersonal dependency tend to covary with emotional distress (Nietzel & Harris, 1990;Santor & Patterson, 2004) and like with other distressed emotional states, it may be possible that loneliness aggravates maladaptive social functioning in individuals exhibiting excessive dependency on others (Overholser, 1996). Individuals with dependent personalities may be at risk for other psychological disorders (Bornstein & Greenberg, 1991;Nietzel & Harris, 1990;Skodol, Gallagher, & Oldham, 1996;Vaillant, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, no study has measured the nature of relation among all three variables. Previous research suggests a shared relationship between loneliness and interpersonal dependency (Mahon, 1982;Overholser, 1996). Thus, it would be useful to determine what is unique and what is shared in their relationship with disordered eating.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it will be useful to integrate the C/I model with other extant frameworks. Although the psychodynamic, cognitive, and behavioral perspectives on dependency are limited in certain respects, each contributes to our understanding of the intra-and interpersonal dynamics of dependent personality traits (see Baltes, 1996;Bornstein, 1996;Overholser, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Notes 1. Although studies indicate that high levels of interpersonal dependency are associated with low self-esteem, and with high levels of need for approval, rejection sensitivity, and narcissism, the magnitudes of these relationships are generally modest, and suggest that dependency does not overlap unduly with these theoretically related traits (see Bornstein, 1992Bornstein, , 1993Bornstein, , 2005Overholser, 1996;and Pincus & Gurtman, 1995, for reviews of research in this area). 2.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial number of studies has now confirmed that the dependent person's self-image as weak and ineffectual and the excessive need to please others contributes to a variety of interpersonal problems and maladaptive consequences (Bornstein, 1999;Overholser, 1996). Bornstein, Riggs, Hill, and Calabrese (1996), for example, demonstrated in a series of experiments how dependent persons might do whatever is necessary when competing with peers to please an authority figure, even if it means acting aggressively.…”
Section: Etiology and Pathologymentioning
confidence: 99%